Online Complaint Management System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A Complaint Management System is considered one of contemporary productivity enhancement gear extensively by means of all companies and management. It provides an online way of solving the problems faced by the public by saving time and eradicate corruption. The objective of complain management system is to make complain easier to coordinate, monitor, track and resolve by tracking the status of complaint done by public to the department.In this portal different-different department will be assigned for complains and administrator of particular department will solve the problem of applicant. If within one week , complain done by applicant is not responded then that complain will automatically gets forwarded to higher authority and then they will solve the problem and also action will be taken against the administrator for not reviewing the complains of the applicant.The System will be able to show the reports like department wise pending complains, closed complains, open complains, and Administrator performance Report.If performance report of Administrator will be remarkable then they will be rewarded for their work.In this portal, separate section will be there that will contain the facilities provided by government for needy people but many are not aware of it. Lot of time and money of public will be saved through the system